YIELD AND NUTRITIONAL QUALITY OF GREENHOUSE LETTUCE AS AFFECTED BY SHADING AND CULTIVATION SEASON - Kosma, C.; Triantafyllidis, V.; Papasavvas, A.; Salahas, G.; Patakas, A. (Emirates Journal of Food and Agriculture, 2017)
Glasshouse experiments were conducted in winter and spring growing seasons in order to evaluate the effects of shading on production and nutritional quality of lettuce (Lactuca sativa L. cv. Parris Island), under Mediterranean climate conditions. In both seasons, plants were cultivated hydroponically under four different levels of photosynthetically active radiation intensities (26, 47, 73 and 100 % of incident light intensity). The results showed that stomatal conductance and photosynthetic rate significantly decreased in shaded plants. This strong negative correlation of leaf physiological parameters with light deficiency resulted in lower biomass yield production in both growing seasons. Moreover, the nutritional value (ascorbic acid concentration) was also significantly decreased in relation to incident light intensity decrease. In contrary, a strong positive correlation of leaf total chlorophyll content and nitrate content with light deficiency was detected. However, nitrate concentration in all treatments remained within the European Union's permissible levels being significantly lower in plants produced in spring compared to winter.